Status, yield gap and way forward of mustard (Brassica juncea) production in India - KUMBHARE, N V; PADARIA, R N; AHMAD, NAFEES; JOSHI, PRATIBHA; PUNITHA, P; SINGH, Y P; SINGH, A K; CHOUDAM, VAISHNAVI (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out to assess the status of rapeseed-mustard (Brassica spp.) using primary and secondary data. The primary data were collected from respondents selected randomly from villages of Muzaffarnagar and Hapur districts of Uttar Pradesh and the secondary data from the Directorate of Economics and Statistics, Department of Agriculture and Cooperation and Farmers’ Welfare, Ministry of Agriculture and Farmers’ Welfare, Government of India. The study revealed that area of rapeseed [Brassica napus (Linn)] and mustard [Brassica juncea (L.) Czenn and Cosson.] in India has increased (343.47%) from 2.07 million hectares in 1950–51 to 9.18 million hectares in 2023–24. Also production of rapeseed and mustard has increased (1644.73 %) from 0.76 million tonnes in 1950–51 to 13.26 million tonnes in 2023–24. In addition, the productivity has increased 4 times from 368 kg/ha in 1950–51 to 1444 kg/ha in 2023–24. Decreasing the yield disparity between the research station, the farmers’ field, and the demonstration plots is the most effective technique for boosting output in a short period of time. The yield gap-I (technology gap) was observed from 150–580 kg/ha and yield gap-II (extension gap) was noticed from 170–600 kg/ha in mustard varieties at farmers’ field. The primary challenges encountered by farmers in western Uttar Pradesh were the higher input costs (65.33%), followed by increasing labour charges (60%) and a high incidence of pests and diseases (51.33%). Implementing targeted extension strategies to reduce yield gaps, as addressing yield gaps in rapeseed and mustard will be vital to enhancing domestic production and achieving greater self-sufficiency in the edible oil market in India.